Sustainable Development in Agribusiness in Indian Market: Use of Communicative Tool/ Informational Communication Technologies (ICT) and digital tools among different category of Indian farmers. - Yadav, Arun; Babu, Jampala Maheshchandra; Kumari R, Dr. Oum (The journal of contemporary issues in business and government, 2022)
Purpose: The objective of the research is to measure the usage of Information Communication Technologies (ICT) and digital instruments in different category of Indian Farmers, to facilitate agribusiness and making it sustainable. The research article also laid emphasis on on the various digital tools and facility available for Indian farmers. Approach and Methodology: The extensive literature review was done before the study to find out what all digital tools and instruments are available for agriculturist in India provided by the regime of the nation or the individual identity. An effort has been made by the researcher to analyse the usage of digital instruments and apps applied by agriculturist in India and also to understand the influence of the same on them. For the same the researcher used questionnaire format. To gather the evidences the scholar selected 509 respondents from Rajasthan territory. The nucleus of the study was whether the different category of farmers is using the digital instruments and apps or not. The scholar used SPSS & ANNOVA or analysis. Findings: As per the evidences of the physical survey, interaction with farmers and outcome of statistical tools, it was found that there is no significant difference in penetration of usage of digital equipment’s and technologies among distinct category of farmers and it has to be uplifted in all level of farmers for the sustainable development in the Agribusinesses. Value and Originality: Digital instruments and applications are the utmost cost saving and time saving gear and provides a different approach for sustainable development. The present study provides a picture of accessible digital instruments and their usage within different category of agrarians. The research paper primarily laid emphasis on the facets which can encourage farmers for the use of digital technologies and helps them in viable agribusiness. The results of the paper will also supports the regime of the nation to find out fissures in the digital program as well as may help in drafting the IT guidelines for sustainable agribusiness. Limitations of the research: It is a non-funded study done by the researcher. Owing to time limitations, the data is being composed from Rajasthan region. Where agriculture and allied services are the major chunk of the economy of the state..